2020
DOI: 10.3389/fimmu.2020.00892
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Influence of Cold Ischemia Time on Outcome After Liver Transplantation for Different Indications—Who Is at Risk? A Collaborative Transplant Study Report

Abstract: Introduction: Despite increasing awareness of the negative impact of cold ischemia time (CIT) in liver transplantation, its precise influence in different subgroups of liver transplant recipients has not been analyzed in detail. This study aimed to identify liver transplant recipients with an unfavorable outcome due to prolonged cold ischemia. Methods: 40,288 adult liver transplantations, performed between 1998 and 2017 and reported to the Collaborative Transplant Study were analyzed. Results: Prolonged CIT si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 24 publications
(58 reference statements)
5
42
1
1
Order By: Relevance
“…ERLT in patients with low lab-MELD scores may achieve similar outcomes to WLT, but ERLT becomes less tolerable with increasing MELD scores [6]. This finding is supported by the results of our previous studies, in which the negative influence of maEDC diminished as the labMELD score decreased, especially in recipients with hepatocellular carcinoma who are generally in a better condition [10][11][12]. However, we could not verify this hypothesis in the case of ERLT because we were not able to analyze the underlying disease, the clinical condition and the MELD score of the recipients, and whether ERL grafts should be preferably allocated to recipients with lower labMELD scores needs to be considered with caution.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…ERLT in patients with low lab-MELD scores may achieve similar outcomes to WLT, but ERLT becomes less tolerable with increasing MELD scores [6]. This finding is supported by the results of our previous studies, in which the negative influence of maEDC diminished as the labMELD score decreased, especially in recipients with hepatocellular carcinoma who are generally in a better condition [10][11][12]. However, we could not verify this hypothesis in the case of ERLT because we were not able to analyze the underlying disease, the clinical condition and the MELD score of the recipients, and whether ERL grafts should be preferably allocated to recipients with lower labMELD scores needs to be considered with caution.…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, similar to WLT, the risk of retransplantation after ERLT is higher in older donors and younger recipients and in recipients of ERL grafts with prolonged cold ischemia times [6,12,52]. Cold ischemia time influences graft and patient survival only during the first year after WLT indicating that once the liver has recovered from the ischemia-reperfusion injurythe duration of the cold storage becomes irrelevant [10]. Although the role of cold ischemia has been fueling intense debate for decades, it has not been addressed properly in ERLT so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DRI and ET-DRI calculations include cold ischemia time, but Feng et al and Braat et al did not consider indication for transplantation as confounder and assumed constant linear influence of cold ischemia time with a fixed coefficient (0.010) [8,9]. By doing so, the categorical effect of cold ischemia could not be observed, especially when opposite, nonlinear influence is evident [73]. In our recent study, we found that the influence of cold ischemia is nonlinear and important only during the first year after liver transplantation and that it also depends on the indication for liver transplantation [73].…”
Section: Discussionmentioning
confidence: 99%
“…By doing so, the categorical effect of cold ischemia could not be observed, especially when opposite, nonlinear influence is evident [73]. In our recent study, we found that the influence of cold ischemia is nonlinear and important only during the first year after liver transplantation and that it also depends on the indication for liver transplantation [73]. This effect was especially strong in patients with hepatocellular carcinoma and alcoholic liver cirrhosis [73].…”
Section: Discussionmentioning
confidence: 99%